Strategi Dakwah Kultural Abdurrahman Wahid: Perspektif Manajemen Dakwah Moderat - Aswari, Nuha Nabila; Handayani, Nur Annisa Tri (IDARI: Jurnal Manajemen Dakwah, 2025)
Abdurrahman Wahid, commonly known as Gus Dur, was an influential Indonesian religious figure and politician who served as president from 1999 to 2001. As a prominent leader of the Nadlatul Ulama (NU), the largest Islamic organization in Indonesia, Gus Dur's da’wah management reflects an inclusive, tolerant, and moderate approach to spreading Islam. A key aspect of his thought is the concept of inclusiveness, which embraces diverse understandings and cultural contexts in conveying Islamic teachings. This research employs qualitative library research, utilizing data from books, journals, and magazines relevant to the topic. Gus Dur emphasized the importance of adapting da’wah to the social and cultural contexts of different communities, advocating for flexibility while adhering to Islamic principles. His da’wah management promotes a tolerant, education-oriented approach, fostering an Islam that is friendly, open, and respectful of differences, while supporting democratic values and human rights. This philosophy significantly encourages interreligious dialogue, tolerance, and harmony among religious communities in Indonesia. The study aims to provide a comprehensive understanding of Abdurrahman Wahid’s da’wah management, highlighting the planning of engaging religious materials and ideas.